THE ABUSE OF DIPLOMATIC IMMUNITIES AMONG STATES: ISSUES AND CHALLENGES - UDEOJI EBELE ANGELA; OCHOGA EDWIN OCHOGA (International Studies Journal)
The paper examined the abuse of diplomatic immunities and privileges among nations. It specifically set out to ascertain the cases of abuse of diplomatic immunity and the implications on the Vienna Convention on Diplomatic Immunity Relations, 1961. The paper adopted the theory of Diplomatic Immunity and argued that immunities and privileges accorded diplomats in the receiving state is for the purpose of effective representation. Thus, the paper revealed that many states have had cases of abuse of diplomatic immunity in the area of criminal and civil crimes. Some of such cases include the killing of an American police, Yvonne Fletcher, Kidnapping of Umaru Dikko and other criminal and civil offenses. Even though the Vienna Convention provided remedies against abuse of diplomatic immunity, cases of abuse are at alarming rate and its poses threat to diplomatic relations among states. The paper concluded that, some diplomats have taken advantage of their immunity to commit crimes and the development is a threat to the sanctity of international law particularly the Vienna Convention on Diplomatic Immunity Relations, 1961 regime. It recommends that every diplomat who commits offense should be met to face the wrath of the law after their sojourn in foreign land.